Are brain metastases a special issue in POLE-mutated endometrial cancer? a case report series - Ebner, Christoph; Lindemann, Kristina; Kristensen, Gunnar; Frosch, Alice; Askautrud, Hanne; Di Santo, Gianpaolo; Leitner, Katharina; Marth, Christian; Zeimet, Alain G. (Frontiers in Oncology, 2025)
POLE-mutated endometrial cancers have repeatedly shown to harbor an excellent prognosis. Recurrences or primary advanced disease are rare events in this subgroup. We report three cases of POLE-mutated endometrioid ECs with brain metastases. While patients with CNS metastases from endometrial cancers are very uncommon and generally confer a poor prognosis and limited survival, all cases presented here survived substantially longer than the median survival time of patients with brain metastasis published in the literature. All patients responded well to systemic therapy or radiotherapy. Additionally, we present one case with complete response to only four cycles of pembrolizumab monotherapy. These cases suggest that, even in the setting of brain metastases or recurrent disease, a pathogenic POLE mutation remains a marker for excellent clinical outcome. The question of why these tumors metastasized to the brain in the first place remains to be answered by further research.